Antibacterial activity of marine bacteria isolated from marine sponges at Phu Quoc island, Vietnam - Hoai Trinh, Phan Thi; Duy Ngoc, Ngo Thi; Ly, Bui Minh; Hung, Le Dinh; Thuy Hang, Cao Thi; Dieu Trang, Vo Thi; Nhu Khanh, Huynh Hoang (Academia Journal of Biology, 2016)
Screening antibacterial activity of fifty marine bacterial strains isolated from twenty-three species of marine sponges from Phu Quoc island. Among them, twenty-one strains (42%) have the ability to inhibit effectively at least two of the ten strains of the tested bacteria. Especially, the strain 045-203-4 showed strong antibacterial activity against six strains of pathogenic bacteria for humans and marine organisms, viz. Pseudomonas aeruginosa, Escherichia coli, Vibrio harveyi, Klebsiella pneumoniae, Bacillus cereus and Streptococcus faecalis. The strain 045-203-4 produced antibacterial with high activity in the medium contained yeast extract (0.8% w/v), glucose (0.5%), pH 7.0 for 30 hours. Analysis of the nucleotide sequence of 16S rRNA gene of strain 045-203-4 showed a strong similarity (99%) with the 16S rRNA gen of Bacillus subtilis. The present investigation reveals that the marine bacteria isolated from marine sponges from Phu Quoc island can be served as a potential source for the study and application of compounds with biological activity.